Sarcoidosis-like reaction induced by immune checkpoint inhibitor in a patient with hepatocellular carcinoma: a case report - Torres-Zurita, Alberto; Vázquez-Montero, Lucía; Gallego-López, Laura; Mediano-Rambla, María Dolores; de la Cruz-Merino, Luis (Frontiers in Immunology, 2023)
Nowadays, immune checkpoint inhibitors (ICI) have become the cornerstone of treatment for many tumors, either as monotherapy or in combination with other therapies. However, these drugs are associated with several new side effects that need early detection.We present the case of a 41-year-old male patient who has been diagnosed with advanced hepatocellular carcinoma (HCC) with metastatic retroperitoneal lymph nodes and a subdiaphragmatic metastatic lesion, undergoing second-line treatment with a combination of nivolumab and ipilimumab. After completing four cycles, the patient was admitted to the hospital due to intermittent fever and profuse sweating. A CT scan showed multiple pathologically enlarged lymph nodes in several locations, raising suspicion of disease progression. The patient's clinical progress was favorable after symptomatic treatment (antipyretics) and was discharged one week after admission. Several days later, the patient complained about painful bilateral ocular redness and was diagnosed with bilateral anterior uveitis. Further blood tests showed elevated angiotensin-converting enzyme (ACE) levels of 67 U/L (normal range: 8 -52) and decreasing alpha-fetoprotein (AFP) levels of 698 ng/mL (previously 1210 ng/mL), indicative of non-progression of the oncological disease. Finally, an excisional biopsy confirmed the presence of non-necrotizing granulomatous lymphadenitis, leading to the diagnosis of sarcoidosis-like reaction (SLR) induced by immunotherapy as the etiology of the polyadenopathy syndrome. SLR, although uncommon, is an adverse effect of ICI treatment resulting from immune system dysregulation, which can mimic disease progression. It is crucial to be aware of this adverse event and to understand the optimal management approach.